Studying the Mediator Role of Religious Orientation on the Customer Loyalty Model - mohammad reza karimi alavijeh; Behrooz Rajabi Bahjat; Mohammad Mehdi Ahmadi (تحقیقات بازار یابی نوین, 2017)
Various factors affecting customer`s loyalty such as quality, trust, credibility and perceived risk. It seems that customer`s religious orientation effect on the effectiveness of these variables on their loyalty. The aim of the present research is to assess the role of religion orientation in relation to the brand and customers’ loyalty in Iran. Statistical population of this research includes all consumers of different beverages in Tehran. Therefore, the sample size of 248 consumers was selected using cluster sampling method. Furthermore, the models of measuring research variables were assessed and tested using exploratory and confirmatory factor analysis method and the research structural model was conducted using structural equation Modeling. Moreover, the methodology used in this research is descriptive-correlational (structural equation modeling approach). The findings indicated that perceived quality and reliability have a positive and meaningful effect on brand credibility, also perceived risk and perceived quality and brand credibility have a positive and meaningful effect on customer loyalty. However, the variable of religious orientation is not confirmed as a meditator variable in the customer loyalty model, and has no significant effect on the relationship between perceived risk, perceived quality and brand credibility with customer loyalty, but this variable acts as an effective meditator on the relationship between reliability and brand credibility.